2005
DOI: 10.1158/1078-0432.ccr-05-0181
|View full text |Cite
|
Sign up to set email alerts
|

Malignant B-Lymphoid Cells with Bone Lesions Express Receptor Activator of Nuclear Factor-κB Ligand and Vascular Endothelial Growth Factor to Enhance Osteoclastogenesis

Abstract: Purpose: Receptor activator of nuclear factor-nB ligand (RANKL) is a key mediator of osteoclastogenesis. Because certain types of tumor cells aberrantly express RANKL, and because bone destruction also develops in B-cell lymphomas of bone origin, we investigated RANKL expression and the mechanisms of osteoclastogenesis in B-lymphoid neoplasms. Experimental Design and Results: Immunohistochemistry of bone specimens resected from patients with primary B-cell lymphoma of bone with bone destruction revealed that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
(23 reference statements)
2
11
2
Order By: Relevance
“…As to the relation of VEGF on the tumor expansion, many studies have suggested its interaction (Grunstein, 1999;Shibata, 2005). The present results strongly support that the observed MALT lymphoma has characteristics as a neoplasm.…”
Section: Discussionsupporting
confidence: 87%
“…As to the relation of VEGF on the tumor expansion, many studies have suggested its interaction (Grunstein, 1999;Shibata, 2005). The present results strongly support that the observed MALT lymphoma has characteristics as a neoplasm.…”
Section: Discussionsupporting
confidence: 87%
“…In our case, we also detected a decreased OPG level in MSCs which increased significantly after treatment. Contrary to previous report by Matsuhashi [9] and Shibata [15], we found no mRNA and protein expression of RANKL in the lymphoma cells which account for more than 50% of the bone marrow mono-nucleated cells before treatment. There has been a controversy whether myeloma cells express RANKL [17].…”
Section: Discussioncontrasting
confidence: 99%
“…It has been demonstrated that stromal/osteoblastic cells and activated T lymphocytes express RANKL in response to cytokines that stimulate bone resorption, such as PTH, dexamethasone, vitamin D3, IL-1, TNF and IL-11 [13,14]. Shibata et al [15] performed immunohistochemistry of bone specimens resected from patients with primary B cell lymphoma of bone with bone destruction revealed that lymphoma cells express RANKL. In our case report, real-time PCR and western blot revealed that expression of RANKL in MSCs decreased sharply after several cycles of chemotherapy accompanied by The protein expressions of DKK-1, RANKL, OPG and PTHrP.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is one of the most potent angiogenic factors produced by tumor cells, including multiple myeloma cells (11,31). In contrast to osteopontin, all multiple myeloma cell lines examined thus far constitutively secrete VEGF (12,32). However, osteoclasts do not produce detectable levels of VEGF.…”
Section: Resultsmentioning
confidence: 99%